PENGARUH EFEKTIVITAS KOMITE AUDIT, KOMITMEN PROFESIONAL, TENURE OF THE AUDIT FIRM, DAN PERSAINGAN ANTAR KANTOR AKUNTAN PUBLIK TERHADAP INDEPENDENSI AKUNTAN PUBLIK: PERSEPSI AUDITOR EKSTERNAL DI SURABAYA - Abadi, Jimy; Hidayat, Widi (JURNAL AKUNTANSI DAN AUDITING, 2011)
Each company which is had by public needs public accountant opinion about financialstatement that was prepared by the management. Audit of financial statement is done forincrease financial statement credibility through push down information risk. Stakeholderslook at independent auditor report for the financial statement include reasonable assuranceabout relevance and reliability. But without independence, the attestation function will be nil.In other words, the independence is perhaps the most essential factor in existence of a publicaccounting profession. The goal of this research are to examine and to get empirical evidenceabout influence of audit committee effectiveness, professional commitment, tenure of the auditfirm, and competition among public accountant firms to accountant public independenceaccordance external auditor perception in Surabaya. The analysis model for this researchuses multiple regression analysis. This research uses 91 samples of questionnaire responsefrom staffs of non big four affiliation and non-affiliation CPA firm. The result of this researchis committee audit effectiveness and commitment professional have significant influence topublic accountant independence individually. Tenure of the audit firm doesn’t havesignificant influence to public accountant independence individually. And the competitionamong public accountant firms has significant influence to public accountant independenceindividually for non affiliation CPA firms, while the competition among public accountantfirms doesn’t have significant influence to public accountant independence individually fornon big four affiliation CPA firms.Keywords:public accountant independence, audit committee effectiveness, professionalcommitment, tenure of the audit firm, competition among public accountant firms,external auditor perception